Constructing two-dimensional CuFeSe2@Au heterostructured nanosheets with an amorphous core and a crystalline shell for enhanced near-infrared light water oxidation. Issue 5 (15th January 2018) - Wen, Huang; Li, Hua; He, Suisui; Chen, Fengjuan; Ding, Erli; Liu, Sha; Wang, Baodui; Peng, Yong
Abstract : The reversed growth of 2D core–shell CuFeSe2 @Au heterostructured nanosheets with a crystalline shell and an amorphous core were first prepared and show enhanced photocatalytic activity for water oxidation under NIR light irradiation. Abstract : Although substantial efforts have been made toward the synthesis of noble metal–semiconductor heteronanostructures, direct in situ synthesis of two-dimensional (2D) core–shell semiconductor@noble metal heterostructured nanosheets remains largely unexplored. Herein, we report the synthesis of a novel 2D core–shell CuFeSe2 @Au heterostructured nanosheet with an amorphous core and a crystalline shell based on the reversed growth of Au nanosheets on the CuFeSe2 frameworks under near-infrared (NIR) illumination. The nanosheet exhibits strong absorbance in the NIR region, and the valence band top of CuFeSe2 @Au nanosheets is higher than the oxidation potential of O2 /H2 O. Owing to the unique structural features, the resulting nanosheets show excellent photocatalytic activity and high stability toward water oxidation with an O2 generation rate up to 3.48 mmol h −1 g −1 compared to those of the constituent materials under NIR light irradiation ( λ > 850 nm). This work brings new opportunities to prepare 2D core–shell semiconductor@noble metal heterostructured nanosheets, which can be applied as photocatalysts toward water splitting and solar energy conversion at long wavelengths.